Influência da dinâmica atmosférica durante eventos de Efeito Secundário do Buraco de Ozônio Antártico sobre o Sul do Brasil - Bittencourt, Gabriela Dornelles (2018)
The Antarctic Ozone Hole (AOH) is a cyclical phenomenon occurring during the austral spring, where a temporary reduction in ozone content is observed in the Antarctic region. However, ozone-depleted air masses can break away from the Ozone Hole and reach midlatitude regions, known as the Secondary Effect of the Antarctic Ozone Hole. Thus, the objective of this dissertation is to show how the stratospheric and tropospheric dynamics behave during the occurrence of this type of event. For this purpose, daily data of the total ozone column were used by the Brewer Spectrophotometer (MKIII # 167) and also OMI satellite, to analyze the data and identify the events of influence of the BOA on the southern region of Brazil. For the analysis of the stratospheric and tropospheric fields, reanalysis data available by the ECMWF and stratospheric fields were used at four different isentropic levels of potential temperature (475 Kelvin, 530 K, 600 K and 700 K). The tropospheric fields were: i) sea level pressure and layer thickness between 1000 and 500 hPa; ii) horizontal cut of the atmosphere (jet at 250 mb and Omega at 500 mb) and iii) vertical cut of the atmosphere (between 1000 and 50 hPa of potential temperature). Thus, 34 events of influence of the Antarctic Ozone Hole that reached the southern region of Brazil were identified for the period of 11 years of data studied (2006 to 2016). Most events (~ 38%) were identified in the month of October, and in September (~ 32.3%) was the second month when most events of the BOA side effect were identified in the region. August and November are the months with the least occurrence of events. In addition, the events showed a predominance of occurrence after the passage of frontal systems (~ 68% of the cases) over the southern region of Brazil, and with the presence of jet stream (polar or subtropical, ~ 91% of cases).